A snapshot (2003-2005) of the 3D postseismic deformation for the 1999, Mw=7.4 Izmit earthquake in the Marmara Region, Turkey, by first results of joint gravity and GPS monitoring - Ergintav, S.; Dogan, U.; Gerstenecker, C.; Cakmak, R.; Belgen, A.; Demirel, H.; Aydin, C.; Reilinger, R. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Gravimetry has the potential to provide important data, in combination with GPS, for detecting vertical surface motions and subsurface mass changes. Here, we focus on the first results of joint gravity and GPS studies in order to understand better the vertical component of the postseismic deformations of the 1999 earthquakes along the western North Anatolian Fault. We investigate the relationship between gravity changes and GPS motions during the period 2003-2005. The changes in this period constitute a snapshot of the nonlinear movements that were not studied before in the Marmara Region. The first observations evaluated here demonstrate that the joint analysis of GPS and gravity data help to constrain the 3D postseismic deformations and hence expand our knowledge of the geophysical process in the Marmara Region. We identify what appear to be different crustal properties in the western and eastern parts of the region. Furthermore, the GPS results indicate that the western extension of the 1999 Izmit rupture area presently has low strain accumulation. To the extent that this behaviour continues through the earthquake cycle, it reduces the moment release of the expected future earthquake in the eastern Marmara seismic gap. In contrast, the western part of Marmara region has important strain loading. While our results are not sufficiently accurate for detailed interpretation, the observed strain accumulation implies the potential for a significant earthquake in the western Marmara region. Generally, possible fault creep extending west of the Izmit fault break following the Izmit earthquake is very important to understand the future seismic hazard in the Marmara region because it reduces the amount of strain accumulation during the earthquake cycle which will either delay the onset of future events or produce smaller future earthquakes. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: gravity; GPS; Izmit earthquake; postseismic deformations; MAGNET; SEA REGION; VISCOELASTIC MODEL; HECTOR MINE; SLIP; CALIFORNIA; MOVEMENTS; DYNAMICS; FAULT; RELAXATION; DUZCE; Geochemistry & Geophysics